Predictions on ultimate strengths and strains of carbon, glass, basalt, PEN, PET, and natural FRP confined circular columns - Girgin, Zehra Canan; Girgin, Konuralp (WILEY, 2025)
In this study, the ultimate strength and strain models, originally developed for carbon and glass fiber-reinforced polymer (CFRP and GFRP) confined circular columns, have been adapted to other recent fiber composite types of basalt, polyethylene naphthalate, polyethylene terephthalate, and natural fibers. The Hoek-Brown strength criterion from rock mechanics, which was extended for the first time to CFRP and GFRP confined concrete, has been applied to almost all fiber types to predict the ultimate strengths through a unified approach. Regression relationships for ultimate strains are also proposed based on a compiled database. The presented models encompass a wide range from low- to high-strength concrete and partially include ultra-high-performance concrete, with very low error rates. The strength and strain models in this study, when compared to the well-known models in the current literature, indicate that especially reported strain models deviate significantly from experimental results. The evaluations of the proposed models reveal a high level of accuracy for every type of fiber.
Keywords: BFRP; CFRP; GFRP; Hoek-Brown criterion; NFRP; PEN; PET; ultimate strain; ultimate strength; AXIAL COMPRESSIVE BEHAVIOR; CONCRETE CYLINDERS; DAMAGED CONCRETE; MODEL; CRITERION; Construction & Building Technology; Engineering